Phylogenetic position of Zygogonium ericetorum (Zygnematophyceae, Charophyta) from a high alpine habitat and ultrastructural characterization of unusual aplanospores. Issue 5 (18th September 2014) - Stancheva, Rosalina; Hall, John D.; Herburger, Klaus; Lewis, Louise A.; McCourt, Richard M.; Sheath, Robert G.; Holzinger, Andreas; Graham, L.
<x xml:space="preserve">Abstract</x> Zygogonium ericetorum, the type species of the genus, was studied from a natural population collected in Mt. Schönwieskopf, Tyrol, Austria. Generic concepts of Zygogonium and Zygnema were tested with atpB, psbC, and rbcL gene sequence analysis, which showed a sister relationship between Z. ericetorum and Mesotaenium, in an early branching clade sister to a grouping of Zygnema and several other filamentous and unicellular zygnematalean taxa. A variety of light, confocal, transmission electron microscopy, and cytochemical techniques provided new data on the variable chloroplast shape of Z. ericetorum, and its aplanospore structure and development, which has been previously considered taxonomically important but has been ambiguously interpreted. Zygogonium can be distinguished from other zygnematophytes (particularly Zygnema), based on the combination of two characters: (i) irregular, compressed plate‐like chloroplasts and (ii) residual cytoplasmic content left in sporangia outside of the fully developed aplanospores or zygospores. The presence of a sporangial wall that separates the spores from the parent cell should be excluded from the definition of Zygogonium, because it is also observed in Zygnema. Similarly, the ecological characterization of Zygogonium as acidophilic is not unique to the genus. The names of 18 species currently belonging to Zygogonium are here changed to Zygnema, because of incompatibility with this new proposed Zygogonium concept. In the species transferred to Zygnema, chloroplasts are typically stellate in three‐dimensions, and the entire content of fertile cells is transformed into the spore, so there is no cytoplasmic residue.